A review of therapeutic potentials of Clinacanthus nutans as source for alternative medicines - Zainol Haida; Mansor Hakiman (Penerbit Universiti Kebangsaan Malaysia, 2019)
Clinacanthus nutans, also known as Sabah Snake Grass, is an ethno-medicinal plant species belonging to the family Acanthaceae and has been widely used as a traditional remedy in Malaysia and Thailand to treat various diseases. The species contains massive amount of phytochemical compounds useful to human health. Various studies have reported that among the compounds found in the species are those with anti-venom properties reported to be rarely present in other medicinal plants. A number of pharmacological research studies have also documented that extracts of C. nutans contain high antioxidants, as well as compounds with anti-cancer, anti-inflammatory and anti-viral properties. Isolation and identification of these phytochemical compounds have gained global attention due to their well-known beneficial values. The present review article is a compilation of previous pharmacological studies on C. nutans with a view of gaining further interest in exploring alternative sources of medicine.